THE CONNECTION BETWEEN MOTIVATION AND JOB PERFORMANCE: A STUDY OF PUBLIC UNIVERSITY LIBRARIANS - Afolabi, Chinedu Emmanuel; Olubunmi , Sarah Adeoye (International Research Journal of Arts and Communication, 2024)
University libraries, as the guardians of knowledge and information, play a pivotal role in shaping the future leaders and knowledge-driven workforce essential for societal progress. These libraries serve as repositories of wisdom, responsible for generating, harnessing, disseminating, and preserving knowledge not only for their academic communities but also for the global society. The core mission of university libraries encompasses the advancement of knowledge frontiers through education, research, and community engagement. This paper underscores the vital significance of university libraries in the knowledge ecosystem. It delves into their multifaceted roles in supporting teaching, facilitating groundbreaking research, and enhancing community service initiatives. The enormity of knowledge derived from these activities underscores the imperative to systematically capture, harness, and safeguard this intellectual wealth. As the custodians of information, university libraries stand as beacons of learning, fostering innovation and intellectual growth. They play a pivotal role in shaping the intellectual landscape of nations and driving societal advancement. This paper explores the indispensable role of university libraries in nurturing the intellectual capital required to navigate the challenges of the modern world and offers insights into their evolving role in the digital age